Emerging temporal trends in tissue plasminogen activator use: Results from the BASIC project. (22nd November 2016) - Domino, Joseph S.; Baek, Jonggyu; Meurer, William J.; Garcia, Nelda; Morgenstern, Lewis B.; Campbell, Morgan; Lisabeth, Lynda D.
Abstract : Objective: To explore temporal trends in tissue plasminogen activator (tPA) administration for acute ischemic stroke (AIS) in a biethnic community without an academic medical center and variation in trends by age, sex, ethnicity, and stroke severity. Methods: Cases of AIS were identified from 7 hospitals in the Brain Attack Surveillance in Corpus Christi (BASIC) project, a population-based surveillance study between January 1, 2000, and June 30, 2012. tPA, demographics, and stroke severity as assessed by the NIH Stroke Scale (NIHSS) were ascertained from medical records. Temporal trends were explored using generalized estimating equations, and adjustment made for age, sex, ethnicity, and NIHSS. Interaction terms were included to test for effect modification. Results: There were 5, 277 AIS cases identified from 4, 589 unique individuals. tPA use was steady at 2% and began increasing in 2006, reaching 11% in subsequent years. Stroke severity modified temporal trends ( p = 0.003) such that cases in the highest severity quartile (NIHSS > 8) had larger increases in tPA use than those in lower severity quartiles. Although ethnicity did not modify the temporal trend, Mexican Americans (MAs) were less likely to receive tPA than non-Hispanic whites (NHWs) due to emerging ethnic differences in later years. Conclusions: Dramatic increases in tPA use were apparent in this community without an academic medical center. Primary stroke center certification likely contributed to this rise. Results suggest that increases in tPA use were greater in higher severity patients compared to lower severity patients, and a gap between MAs and NHWs in tPA administration may be emerging.